Development of a digital framework for the computation of complex material and morphological behavior of biological and technological systems. (March 2015) - Ahlquist, Sean; Kampowski, Tim; Oliyan Torghabehi, Omid; Menges, Achim; Speck, Thomas
Abstract: Research in material behavior involves the study of relationships between material composition and capacities to negotiate internal and external pressures. Tuning material composition for performance allows for the integration of multifaceted functionality and embedded responsiveness within minimal material means. The relationships of material composition and system performance can be dissected into properties of topology (in count, type and association), forces (as the simulation of contextual pressures ), and materiality (material properties and constraints of fabrication). When resourcing information about these aspects of material behavior from biological or technological systems, the physical precedents, as specimens and/or models, serve as the primary, and often sole, exemplar. While this is necessary to initiate the study of material make-up as it relates to specific morphological performance, there is an inherent limit when asking how and to what degree the knowledge resourced from that instance applies when alterations from the norm are generated. This research proposes the possibility for testing variants of a morphological system using physical models as the precedent while incorporating multiple means of computational analysis for extensive exploration. The framework begins with the initial stage of deducing principles, regarding material organization and behavior, through comparative physical and computational study. Subsequently, through methods of abduction, new vocabularies of form and potentials in performance are generated primarily through computational exploration. The framework is shaped by research into the design and materialization of complex pre-stressed form- and bending-active architectures. A novel aspect of this framework is the development of a software environment called springFORM . In this environment, material behavior is simulated using basic spring-based (particle system) methods. The novel contribution of this software is in providing means for both manual and algorithmic manipulations of mesh topologies and material properties during the form-finding process. A series of architectural prototypes, which range in scale, define rules for the relationship between topological-material complexity and the sequencing of particular exploratory methods. The studies define the value of the physical precedent as it engenders further material prototypes, spring-based explorations and simulations with finite element analysis. These rules and methods are further elaborated upon through studying the particularly fascinating structural capacity of banana leaf stalks, a material system which is stiff in bending yet highly flexible in torsion. Of interest is a functional robustness which allows for the negotiation of both self-weight and wind loading for a large and fully integrated leaf structure. Methods of simulation and meta-heuristics are developed to address the continual material and topological differentiation of the banana leaf stalk. Case studies are based upon examination of specimens from the species Musa acuminata and Ensete ventricosum. Mechanical properties and geometric descriptions of isolated moments within the stalk provide the basis for computational comparison. Fundamental properties and behaviors are extracted from the plant specimens, yet a full description is not possible because of the plant's intricate spatial structure. In this case, the computational means serve to elucidate upon the behavior of the complete system as well as provide avenues for exploring its variants. This paper describes an extensible and calibrated framework which can foster enhanced biomimetic insights by explorations which are based upon but extend well beyond initial biological and/or technological precedents. Highlights: A physical/digital framework is developed for form- and bending-active architectures. Banana leaf stalks (petioles) are researched for their robust structural capacities. Spring-based software, called springFORM, is utilized to simulate a variety of material behaviors. The extensible and calibrated framework fosters enhanced biomimetic insights.